Preliminary study on insecticide susceptibility status of The Black fly, Simulium (Simulium) Vanluni (Diptera: Simuliidae) in Malaysia - Chen, Chee Dhang; Takaoka, Hiroyuki; Lau, Koon Weng; Low, Van Lun; Chin, Ai Chdon; Azidah, Abdul Aziz; Sofian-Azirun, Mohd (2018)
Susceptibility status of Simulium (Simulium) vanluni (Diptera: Simuliidae) adults obtained from Pahang, Malaysia was evaluated against 11 adulticides representing four major insecticide classes: organochlorines (DDT and dieldrin), organophosphates (malathion and fenitrothion), carbamates (bendiocarb and propoxtlr) and pyrethroids (etofenprox, deltamethrin, Iambdacyhalothrin, permethrin and cyfluthrin). The adult bioassay was conducted according to WHO standard protocol to determine the insecticide susceptibility. Mortality at 24 h post treatment was used as indicator for susceptibility status. Simulium vanluni populations in Pahang exhibited different levels of resistance against II adulticides with mortality ranged from 60.00 to 100.00%. Simulium vanluni was susceptible to propoxur, cyfluthrin and bendiocarb with 100% mortality, but resistant to other adulticides with <98% mortality. The susceptibility status ofS. vanluni in descending order was propoxur, cyfluthrin > bendicarb > deltamethrin > lambdacyhalothrin > pennethrin > etofenprox > DDT > malathion > fenitrothion > dieldrin. Regular surveys should be conducted to monitor the susceptibility status of this insect vector to prevent further development of resistance.